2003
DOI: 10.1007/bf02897920
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between questionnaire survey results of vibration complaints of wheelchair users and vibration transmissibility of manual wheelchair

Abstract: Objective: Clarify the relation between the complaints of wheelchair users and the vibration characteristics of the wheelchair, to improve wheelchair comfort and design.Methods: The questionnaires were distributed to 33 wheelchair users directly by the experimenter in order to identify the causes of complaints from wheelchair vibrations that they experienced. The vibration transmissibility of wheelchairs of ten subjects was measured to clarify the causes of complaints of wheelchair vibration according to the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 5 publications
2
24
0
2
Order By: Relevance
“…However, tilt‐in‐space wheelchair users spend large periods of time in their chair, so even small reductions in shock and vibration most likely have positive health benefits. As previously identified, besides improving comfort, potential health benefits include, but are not limited to, reductions in low back pain, neck pain, muscle fatigue, early degeneration of the lumbar spine, herniated lumbar discs, and spinal discomfort and pain [3‐11]. Future research should explore the mechanisms of injury caused by shock and vibration exposure in the wheelchair population, and determine a reduction necessary for health benefits and a standard protocol for evaluating wheelchair exposure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, tilt‐in‐space wheelchair users spend large periods of time in their chair, so even small reductions in shock and vibration most likely have positive health benefits. As previously identified, besides improving comfort, potential health benefits include, but are not limited to, reductions in low back pain, neck pain, muscle fatigue, early degeneration of the lumbar spine, herniated lumbar discs, and spinal discomfort and pain [3‐11]. Future research should explore the mechanisms of injury caused by shock and vibration exposure in the wheelchair population, and determine a reduction necessary for health benefits and a standard protocol for evaluating wheelchair exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Some secondary health conditions may be induced by repeated shock and vibration exposure. Instantaneous peak acceleration, or shock, and whole‐body vibration exposure has been correlated to low back pain, neck pain, muscle fatigue, early degeneration of the lumbar spine, herniated lumbar discs, and spinal discomfort and pain [3‐11]. The International Organization for Standardization (ISO) established methods to quantify shock and whole‐body vibration exposure and the risks associated with exposure in ISO 2631‐1 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wheelchair users can also be exposed to harmful whole-body vibrations due to irregularities in the road and obstacles during wheelchair usage in outdoor conditions. Research has focussed on quantifying the wheelchair vibration characteristics in the laboratory [72] and in (simulated) outdoor conditions, driving over different road conditions [73] and typically experienced obstacles [74]. Some evidence is available for the influence of driving on head balance.…”
Section: Dynamic Environmentsmentioning
confidence: 99%
“…And found that using surveys to establish baseline communication levels with neighbors could advance public relations for mining operations by providing insight and direction for site specific public relations programs. Maeda, et al [35] conducted the questionnaires distributed to 33 wheelchair users directly by the experimenter in order to identify the causes of complaints from wheelchair vibrations that they experienced. Khan and Sundström [36] studied three hundred thirty Swedish passengers using a questionnaire survey on vibration comfort in Swedish Inter-City Trains.…”
Section: Introductionmentioning
confidence: 99%